2020
DOI: 10.1109/access.2020.2998839
|View full text |Cite
|
Sign up to set email alerts
|

A Data Augmentation Method Based on Generative Adversarial Networks for Grape Leaf Disease Identification

Abstract: The identification of grape leaf diseases based on deep learning is critical to controlling the spread of diseases and ensuring the healthy development of the grape industry. Focusing on the lack of training images of grape leaf diseases, this paper proposes a novel model named Leaf GAN, which is based on generative adversarial networks (GANs), to generate images of four different grape leaf diseases for training identification models. A generator model with degressive channels is first designed to generate gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(46 citation statements)
references
References 42 publications
(50 reference statements)
1
33
0
Order By: Relevance
“…In addition, dense connection was added to the generator and discriminator to enhance the information input of each layer and significantly improve the classification performance. Liu et al [36] added dense connections in GAN, and improved the loss function to generate grape leaves to achieve better recognition results in the same recognition network. However, the goal of GAN is to generate images that are as real as possible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dense connection was added to the generator and discriminator to enhance the information input of each layer and significantly improve the classification performance. Liu et al [36] added dense connections in GAN, and improved the loss function to generate grape leaves to achieve better recognition results in the same recognition network. However, the goal of GAN is to generate images that are as real as possible.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper [34], four different kinds of grape leaf disease images were expanded by a novel Leaf GAN model. The experimental results showed that the Leaf GAN model could make the grape leaf disease images highlight the disease and generate enough grape leaf disease images.…”
Section: ) Generate Adversarial Network (Gans)mentioning
confidence: 99%
“…A maize leaf feature enhancement framework was designed first which enhanced the maize features under the complex environment and then designed an AlexNet architecture network named DMS-Robust AlexNet, which improved the capability of feature extraction combined with dilated convolution and multiscale convolution. Liu, B et al [7] proposed a generative adversarial network-based leaf disease identification model. This model generated images of four different leaf diseases for training, then fused DenseNet and instance normalization to identify real and fake disease images as well as feature extraction capability on grape leaf lesions.…”
Section: Introductionmentioning
confidence: 99%